Antiviral therapy for genital herpes infections in pregnancy. Issue 3 (June 2005) - Baker, David A
One of the most deleterious consequences of maternal infection with herpes simplex virus is neonatal herpes, which results in death or significant neurodevelopmental impairment in the majority of infected babies. Herpes simplex virus infection during pregnancy can also impact the psychologic health of the mother. The ability to minimize the risk of herpes simplex virus transmission has improved in tandem with advances in understanding of the mechanisms and epidemiology of acquisition of neonatal herpes simplex virus. In particular, antiviral pharmacotherapy is now recognized as an important option both for reducing the risk of transmission of herpes simplex virus from a seropositive to a seronegative partner and, potentially, for modifying several risk factors for transmission of the virus from a herpes simplex virus-infected mother to the neonate. This review discusses the consequences and management of herpes simplex virus infection during pregnancy, with a focus on the evolving role of antiviral therapy.